THE ROLE OF THE COMMUNITY IN ENVIRONMENTAL MANAGEMENT IN THE COASTAL AREA OF RUPAT DISTRICT - Lamun Bathara; Syahril Nedi; Irwan Effendi; Musyirna Rahmah NST; Tio Afandi Nasution; Afrizal Tanjung (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2025)
Coastal environmental problems in Rupat District cannot be resolved solely through a top-down approach or government intervention. This study was conducted in 2025 with the intention of comprehensively analyzing the role of the community in environmental management in the coastal areas of Rupat District, particularly on Ketapang and Lancah beaches. Through a systematic research approach, this study aims to identify the forms of community roles in coastal environmental management efforts, analyze factors that influence the level of community participation, describe the various challenges faced in implementing community-based environmental management, and formulate strategies for strengthening community roles that can be implemented sustainably. The method used in this study was a survey method with a total of 31 respondents, consisting of fishermen, seaweed farmers, fish traders, community leaders, and people involved in marine tourism activities. The results of the study can be concluded that community-based coastal environmental management has enormous potential but faces complex structural challenges